Stability of the administrative act of particular content evaluated in connection with the general interest and the collective rights - Limas Suárez, Adriana Rocio (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The stability is not preached of the administrative acts of particular and concrete char acter, when the same ones affect general and collective rights of interest. The above-men tioned finds legitimate sustenance in the application of constitutional fundamental prin ciples foreseen in the articles 1°, 2° of the Political Constitution, laid the foundation in the Social State of Right and as such been founded in the prevalence of the general interest, in turn the principle consigned in the article 58, whereby when the application of a law passed for reasons of public utility or social interest, results in conflict the right of those peculiar with the need for it, the private interest must yield to the public or social interest. Therefore the direct revocation of the administrative acts of particular character without their holder's consent, through case-law, proceeds when it is evident the threat or viola tion of the general interest.